2010
DOI: 10.1055/s-0029-1243937
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of confocal endomicroscopy in celiac disease

Abstract: The assessment of duodenal histology by CEM in patients with celiac disease is sensitive and specific in determining increased numbers of IELs and villous atrophy, but insufficient in respect of crypt hyperplasia. For routine use of CEM in patients with celiac disease, the technique would need to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
(28 reference statements)
0
28
0
2
Order By: Relevance
“…Still, eCLE showed high accuracy to diagnose celiac disease, and in patients with established celiac disease even a trend towards higher accuracy for CLE versus histopathology was reported due to sampling error for biopsies. These results have been confirmed in followup trials with respect to villous atrophy and intraepithelial lymphocytes, but not crypt hyperplasia [44]. CLE has even been studied in children for the diagnosis of celiac disease.…”
Section: Endomicroscopy Of the Small Intestinementioning
confidence: 64%
“…Still, eCLE showed high accuracy to diagnose celiac disease, and in patients with established celiac disease even a trend towards higher accuracy for CLE versus histopathology was reported due to sampling error for biopsies. These results have been confirmed in followup trials with respect to villous atrophy and intraepithelial lymphocytes, but not crypt hyperplasia [44]. CLE has even been studied in children for the diagnosis of celiac disease.…”
Section: Endomicroscopy Of the Small Intestinementioning
confidence: 64%
“…Another study recently reviewed the sensitivity and specificity of eCLE in the evaluation of established CD. 48 In addition to villous atrophy, this study was able to identify IEL using CLE and maybe useful for diagnosing Marsh I CD. However, crypt hypertrophy had a lower sensitivity and specificity than Leong's study.…”
Section: Coeliac Diseasementioning
confidence: 78%
“…3d,e) when using intravenous fluorescein as a contrast agent. Other studies have shown that endomicroscopy can diagnose coeliac disease [55][56][57][58] based on recognition of features relevant to EED, such as villous atrophy, crypt hyperplasia and lymphocyte infiltration. In particular, Venkatesh et al 58 reported successful diagnosis of coeliac disease (100% sensitivity, 80% specificity) in children as young as 1.8 years of age.…”
Section: Microbiota Changesmentioning
confidence: 99%